До характеристики сучасного стану забезпечення прав та свобод дитини в Україні - Могилевська, Л. Г.; Mohylevska, L. H. (Юридичний бюлетень. - 2018. - Вип. 8. - С. 59-65, 2018)
Надано характеристику сучасного стану забезпечення прав та свобод дитини в Україні. Визначено, що найголовнішою проблемою є незатверджені спеціальні програми щодо захисту дітей, які проживають у зоні проведення антитерористичної операції. Військово-цивільні адміністрації не мають спеціальних повноважень та кадрового забезпечення для вжиття ефективних заходів із захисту дітей від наслідків збройного конфлікту. Наголошено, що за час незалежності України законодавець створив досить потужну та розгалужену систему захисту прав та свобод дітей, яка складається з нормативно-правових актів різної юридичної сили. Однією із проблем у цій сфері є фактична відсутність правових норм, які встановлюють особливості правового регулювання прав дітей в умовах збройного конфлікту, зокрема за умов проведення антитерористичної операції. Крім того, особливої уваги потребує нормативно-правове врегулювання сфери наукового, інформаційно-методичного, кадрового забезпечення галузі охорони та захисту прав і свобод дитини.

In the article, based on the analysis of scientific views of scientists and the norms of the current legislation, the characteristics of the current state of ensuring the rights and freedoms of the child in Ukraine are given. It was determined that the main problem is the lack of approved special programs for the protection of children living in the area of the anti-terrorist operation, the military-civilian authorities do not have special powers and staffing for effective measures to protect children from the consequences of an armed conflict. Official records of children who died and were injured as a result of armed conflict were not kept in Ukraine. Legislation does not establish a punishment for committing a criminal offense in the form of recruiting, recruiting and recruiting children in hostilities. It was clarified that a number of laws were passed at the legislative level, the norms of which are aimed at protecting the rights and freedoms of the child, which can undoubtedly be assessed positively. At the same time, the said acts do not limit the list of legal acts in this area. An important group is also subordinate legal acts. The priorities of the rights and freedoms of the child in Ukraine are as follows: creation of favorable conditions for the child’s life and development, creation of a child-friendly justice system, creation of a safe information space for children, activation of the territorial community in solving the issues of children’s rights in the conditions of decentralization. It is concluded that during the independence of Ukraine, the legislator has created a rather powerful and extensive system of protection of children’s rights and freedoms, which consists of normative legal acts of various legal force. One of the problems in this area is the actual absence of legal norms that establish the peculiarities of the legal regulation of the rights of children in conditions of armed conflict, in particular, in the context of a counter-terrorist operation. In addition, the normative and legal regulation of the sphere of scientific, informational and methodological, personnel provision of the area of protection and protection of children’s rights and freedoms is required.

Дана характеристика современного состояния обеспечения прав и свобод ребенка в Украине. Определено, что главной проблемой являются неутвержденные специальные программы защиты детей, проживающих в зоне проведения антитеррористической операции. Отмечено, что за время независимости Украины законодатель создал достаточно мощную и разветвленную систему защиты прав и свобод детей, состоящую из нормативно правовых актов разной юридической силы. Одной из проблем в этой сфере является фактическое отсутствие правовых норм, устанавливающих особенности правового регулирования прав детей в условиях вооруженного конфликта, в частности, при проведении антитеррористической операции. Особого внимания требует нормативно-правовое урегулирование сферы научного, информационно-методического, кадрового обеспечения области охраны и защиты прав и свобод ребенка.
On characteristics of the current state of enforcement of children’s rights and freedoms in Ukraine
Keywords: права та свободи; rights and freedoms; права и свободы; дитина; child; ребенок; забезпечення прав та свобод дитини; ensuring the rights and freedoms of the child; обеспечение прав и свобод ребенка; законодавство; legislation; законодательство; нормативно-правове регулювання; normative and legal regulation; нормативно-правовое регулирование